Joint R&D subsidies, related variety, and regional innovation - Tom Broekel; Matthias Brachert; Matthias Duschl; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2015)
Subsidies for R and D are an important tool of public R and D policy, which motivates extensive scientific analyses and evaluations. The paper adds to this literature by arguing that the effects of R and D subsidies go beyond the extension of organizations' monetary resources invested into R and D. It is argued that collaboration induced by subsidized joint R and D projects yield significant effects that are missed in traditional analyses. An empirical study on the level of German labor market regions substantiates this claim showing that collaborative R and D subsidies impact regions' innovation growth when providing access to related variety and embedding regions into central positions in cross-regional knowledge networks.
Keywords: L14; O31; R12; 330; collaborative R and D projects; related variety; regional innovation